The Role of Indonesian National Library in Preserving and Disseminating Manuscripts - Alfida, Alfida (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2014)
The Indonesian National Library has undertaken the preservation of Indonesian manuscripts through collection and digitization efforts across regions such as Yogyakarta, East Sumatera, Cirebon, and Pulau Penyengat. However, substantial work remains to be done given the extensive number of manuscripts in Indonesia. Surprisingly, this issue is not adequately addressed by the national library, with dissemination efforts lagging behind. While an online catalog for the manuscripts exists, it is significantly less comprehensive than its printed counterpart, and electronic files are often unavailable. This paper explores several key areas: firstly, the landscape of manuscripts in Indonesia; secondly, the intended role of the national library in preservation and dissemination; thirdly, the challenges surrounding the collection itself, including the condition of the manuscripts and the opportunities they present for research; and finally, the potential for collaboration to establish a regional portal or virtual repository for manuscripts in Southeast Asia.